Business performance measurement theory and practice - Neely, Andy D. 1967- (Cambridge University Press, 2002)
The field of performance measurement has evolved rapidly in the last few years with the development of new measurement frameworks and methodologies, such as the balanced scorecard, the performance prism, economic value added, economic profit, activity based costing and self-assessment techniques. This multidisciplinary, international book draws together the key themes to provide an up-to-date summary of the leading ideas in business performance measurement, theory and practice. It includes viewpoints from a range of fields including accounting, operations management, marketing, strategy and organisational behaviour. The book will appeal to graduate students, managers and researchers interested in performance measurement, whatever their discipline